Effects of joint moments on horizontal and vertical velocities of body mass center during jumping in different directions - Suzuki, Y.; Kobayashi, Y.; Takizawa, M. (International Journal of Sport & Health Science, 2018)
The purpose of this study was to elucidate the effects of the lower limb joint moments on the horizontal and vertical velocities of the body mass center during jumping in different directions. Ten male university students performed forward, vertical, and backward jumps, during which their jumping motion (150 Hz) and ground reaction force (600 Hz) were collected. Induced acceleration analysis was performed to quantify the body mass center velocity produced by each joint moment. In all jump conditions, the hip, knee, and ankle joints exerted extension and plantarflexion moments, and most of vertical velocity of the body mass center was produced by the ankle moment. Additionally, the knee moment produced backward velocity and the ankle moment produced forward velocity, while the hip moment produced neither horizontal nor vertical velocities. These results indicate that the knee moment accelerates the body mass center backward and the ankle moment accelerates it upward and forward, regardless of jumping direction. Although there was no significant difference in the peak joint moments, significant differences were observed in the horizontal velocities produced by the knee and ankle moments. Moreover, significant differences were observed in the forward lean angle of the trunk at the beginning of the jump motion and lower limb segments at take-off. These results indicate that the velocity of body mass center was affected by not only the joint moments but also body configuration.